Perfluorinated Cobalt Phthalocyanine Effectively Catalyzes Water Electrooxidation. Issue 1 (8th December 2014) - Morlanés, Natalia; Joya, Khurram S.; Takanabe, Kazuhiro; Rodionov, Valentin
Abstract: Efficient electrocatalysis of water oxidation under mild conditions at neutral pH was achieved by a fluorinated cobalt phthalocyanine immobilized on fluorine‐doped tin oxide (FTO) surfaces with an onset potential at 1.7 V vs. RHE. Spectroscopic, electrochemical, and inhibition studies indicate that phthalocyanine molecular species are the operational active sites. Neither free cobalt ions nor heterogeneous cobalt oxide particles or films were observed. During long‐term controlled‐potential electrolysis at 2 V vs. RHE (phosphate buffer, pH 7), electrocatalytic water oxidation was sustained for at least 8 h (TON ≈ 1.0 × 10 5 ), producing about 4 μmol O2 h –1 cm –2 with a turnover frequency (TOF) of about 3.6 s –1 and no measurable catalyst degradation. Abstract : Water oxidation is efficiently electrocatalyzed by a fluorinated cobalt phthalocyanine (CoFPc) immobilized on fluorine‐doped tin oxide surfaces. CoFPc molecular species are revealed as the operational active sites. At 2 V (vs. RHE, pH 7), electrocatalytic water oxidation is sustained for at least 8 h (TON ≈ 1.0 × 10 5 ), producing about 4 μmol O2 h –1 cm –2 with no measurable catalyst degradation.